2018
DOI: 10.3390/ijms19092716
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-Mediated Multiplex Genome Editing of the BnWRKY11 and BnWRKY70 Genes in Brassica napus L.

Abstract: Targeted genome editing is a desirable means of basic science and crop improvement. The clustered, regularly interspaced, palindromic repeat (CRISPR)/Cas9 (CRISPR-associated 9) system is currently the simplest and most commonly used system in targeted genomic editing in plants. Single and multiplex genome editing in plants can be achieved under this system. In Arabidopsis, AtWRKY11 and AtWRKY70 genes were involved in JA- and SA-induced resistance to pathogens, in rapeseed (Brassica napus L.), BnWRKY11 and BnWR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(65 citation statements)
references
References 82 publications
0
65
0
Order By: Relevance
“…Sequencing of Brassica genomes has resulted in reference genome sequences for B. napus (Bayer et al ., ; Chalhoub et al ., ; Sun et al ., ), B. rapa (Cai et al ., ; Wang et al ., ), B. oleracea (Liu et al ., ; Parkin et al ., ), B. juncea (Yang et al ., ) and B. nigra (Yang et al ., ), permitting a comprehensive study of R‐genes in these Brassica species. For example, Alamery et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequencing of Brassica genomes has resulted in reference genome sequences for B. napus (Bayer et al ., ; Chalhoub et al ., ; Sun et al ., ), B. rapa (Cai et al ., ; Wang et al ., ), B. oleracea (Liu et al ., ; Parkin et al ., ), B. juncea (Yang et al ., ) and B. nigra (Yang et al ., ), permitting a comprehensive study of R‐genes in these Brassica species. For example, Alamery et al .…”
Section: Introductionmentioning
confidence: 99%
“…Sequencing of Brassica genomes has resulted in reference genome sequences for B. napus Chalhoub et al, 2014;Sun et al, 2018), B. rapa (Cai et al, 2017;Wang et al, 2011), B. oleracea Parkin et al, 2014), B. juncea (Yang et al, 2016) and B. nigra (Yang et al, 2016), permitting a comprehensive study of R-genes in these Brassica species. For example, Alamery et al (2017) found 641, 443 and 249 NBS-LRR genes in B. napus, B. oleracea and B. rapa, respectively, while Yu et al (2014) identified 157, 206 and 167 NBS-LRR genes in B. oleracea, B. rapa and A. thaliana, respectively, which may be due to using different approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The application of CRISPR-Cas9-targeted mutagenesis in plants has been reported not only in Arabidopsis (Fauser et al, 2014;Feng et al, 2014) but also in crops like wheat (Wang et al, 2014), tomato (Brooks et al, 2014), and rice (Li et al, 2016). In rapeseed, some few studies have already presented targeted genome editing mediated by the CRISPR/Cas9 system (Braatz et al, 2017;Okuzaki et al, 2018;Sun et al, 2018). Therefore, as more and more genes are identified for their function, mutagenesis in rapeseed plant breeding could be managed by more efficient ways than chemical/physical and random ways.…”
Section: Discussionmentioning
confidence: 99%
“…In B. napus, a few studies have utilized CRISPR/Cas9 system for editing genes associated with plant/pod development (ALCATRAZ, GA1-3, FRUITFULL, DA1, DA2, CLAVATA, and SPL3), fatty acid synthesis (BnFAD2), and biotic stress response (BnWRKY11and -70) (Sun Q. et al, 2018). The application of CRISPR-Cas9 for climate-resilient transgenic production is yet to be reported in canola ( Table 5).…”
Section: Genome Editing Techniquesmentioning
confidence: 99%